A fragment-like approach to PYCR1 inhibition. Issue 18 (15th September 2019) - Milne, Kirsty; Sun, Jianhui; Zaal, Esther A.; Mowat, Jenna; Celie, Patrick H.N.; Fish, Alexander; Berkers, Celia R.; Forlani, Giuseppe; Loayza-Puch, Fabricio; Jamieson, Craig; Agami, Reuven
Graphical abstract: Highlights: Higher levels of protein are found in certain types of cancer. This is attributed to overexpression of a key protein involved in proline biosynthesis. Focused screening has for the first time identified a small fragment-like inhibitor (ProPI-1) of this protein target. Mechanistic studies show ProPI-1 can attenuate proline biosynthesis in relevant cell types. Phenotypic studies reveal that ProPI-1 can control cell proliferation in two different breast cancer cell types. Abstract: Pyrroline-5-carboxylate reductase 1 (PYCR1) is the final enzyme involved in the biosynthesis of proline and has been found to be upregulated in various forms of cancer. Due to the role of proline in maintaining the redox balance of cells and preventing apoptosis, PYCR1 is emerging as an attractive oncology target. Previous PYCR1 knockout studies led to a reduction in tumor growth. Accordingly, a small molecule inhibitor of PYCR1 could lead to new treatments for cancer, and a focused screening effort identified pargyline as a fragment-like hit. We report the design and synthesis of the first tool compounds as PYCR1 inhibitors, derived from pargyline, which were assayed to assess their ability to attenuate the production of proline. Structural activity studies have revealed the key determinants of activity, with the most potent compound (4 ) showing improved activity in vitro in enzyme (IC50 = 8.8 µM) and pathway relevant effects in cell-based assays.